2005
DOI: 10.1120/jacmp.2026.25364
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver variation in cervical cancer tumor delineation for image-based radiotherapy planning among and within different specialties

Abstract: Radiation therapy for cervical cancer involves a team of specialists, including diagnostic radiologists (DRs), radiation oncologists (ROs), and medical physicists (MPs), to optimize imaging‐based radiation therapy planning. The purpose of the study was to investigate the interobserver variations in tumor delineation on MR images of cervical cancer within the same and among different specialties. Twenty MRI cervical cancer studies were independently reviewed by two DRs, two ROs, and two MPs. For every study, ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…MRI sequences for radiotherapy delineation purposes are usually T2-weighted ( 80 83 ). The choice of coil has varied throughout the literature, with details often not provided; however, when described, generally in more recent investigations ( 84 ), it was usually a body coil with phased array coils.…”
Section: Resultsmentioning
confidence: 99%
“…MRI sequences for radiotherapy delineation purposes are usually T2-weighted ( 80 83 ). The choice of coil has varied throughout the literature, with details often not provided; however, when described, generally in more recent investigations ( 84 ), it was usually a body coil with phased array coils.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors have suggested training with or close collaboration with a radiologist when contouring. 78,91,92 The use of multimodality imaging is becoming standard in radiation oncology and attention must be paid to both image registration and interpretation. Departmental links with radiologists and PET physicians are helpful in this regard, with the ideal scenario being the presence of these specialists at the radiation oncology peer review meeting.…”
Section: Discussionmentioning
confidence: 99%
“…found that collaborative tumour delineation in lung cancer changed contouring in 19/20 cases. Some authors have suggested training with or close collaboration with a radiologist when contouring . The use of multimodality imaging is becoming standard in radiation oncology and attention must be paid to both image registration and interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…2 Target volume uncertainty of potential centimetres may overshadow the millimetre accuracy associated with planning and delivery of radiation. 3 Delivery of radiotherapy is highly accurate, uncertainty associated with modern radiotherapy is usually <3% of the dose prescribed and geometric uncertainty is usually within 3 mm. 4 In contrast, variability associated with cervical cancer target volumes are potentially of a larger magnitude compared to other uncertainties; a study of cervical cancer target volumes showed a distance between contours of up to 30-40 mm.…”
Section: Introductionmentioning
confidence: 99%